Empowering Women Entrepreneurs in Emerging Economies: a Conceptual Model - Ajjan, Haya; Beninger, Stefanie; Mostafa, Rania; Crittenden, Victoria L. (Organizations and Markets in Emerging Economies, 2014)
Cyberfeminism is a woman-centered perspective that advocates women’s use of new information and communications technologies for empowerment. This paper explores the role of information technologies, in particular the role of social media, in empowering women entrepreneurship in emerging economies via increased social capital and improved self-efficacy. A conceptual model is offered and propositions are explicated.